In vitro and In vivo neuroprotective study of solid lipid nanoparticles loaded with dimethyl fumarate (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Dimethyl fumarate (DMF) is a FDA approved oral medication used to treat patients with multiple sclerosis (MS). Biological half-life of DMF is about 1 h, and it is rapidly hydrolyzed to its active metabolite monomethyl fumarate. The objective of present study is to formulate and characterize DMF loaded solid lipid nanoparticles (SLNs) to overcome these limitations. Material and Methods: DMF loaded SLNs were prepared by hot microemulsion and sonication method. Stearic acid was used as lipid and soy lecithin was colipid. Results and Discussion: The synthesized SLNs offered an average particle size of 300 nm, polydispersity index